PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN TOTAL ASSET TURNOVER TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ismanto, Aprina; Hernadi Moorcy, Nadi (Fakultas Ekonomi Universitas Balikpapan, 2023)
The Influence of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Profit Growth in Pharmaceutical Sub-Sector Companies Listed on the Indonesia Stock Exchangeâ€. The purpose of this study was to determine the influence of the current ratio, debt to equity ratio, and total asset turnover on profit growth in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. The object of this study is the pharmaceutical sub-sector companies, which total 11 companies by taking the sample criteria into 10 companies. The data used in this research is secondary data obtained from the 2018-2021 financial reports. The data is processed using multiple linear regression analysis with the classical assumption test, the coefficient of determination test, the correlation coefficient test, the f test, and the t test. The data is managed using the SPSS Statistics 25 application tool. Based on the results of the test, the debt to equity ratio has a significant effect on profit growth, while the current ratio and total asset turnover have no significant effect on profit growth.